2008
DOI: 10.1063/1.2963367
|View full text |Cite
|
Sign up to set email alerts
|

Multiple negative resistances in trenched structures bridged with carbon nanotubes

Abstract: Field effect transistor (FET)-like structures with a trench as “gate” were fabricated on GaAs substrates. The bottom of the trench as well as the “source” and “drain” regions were metallized. Bundles of nanotubes were then suspended over the trench. At a certain threshold, these trenched FET-like structures display an S-shaped negative resistance, which breaks into parallel branches when the voltage is increased in equal steps. Several such steps were observed at room temperature and under normal pressure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In fact, transistor action was first demonstrated in carbon nanotubes [6], and regarding RF applications [7], [8], it has been recently shown that FM and digital radio demodulation is possible using carbon nanotubes nanoelectromechanical systems [9] (see Figure 3). Gate Length 240 nm 550 nm RF/microwave technology will be fundamentally influenced by nanotechnology.…”
Section: Mission Of Tc Mtt-25mentioning
confidence: 98%
“…In fact, transistor action was first demonstrated in carbon nanotubes [6], and regarding RF applications [7], [8], it has been recently shown that FM and digital radio demodulation is possible using carbon nanotubes nanoelectromechanical systems [9] (see Figure 3). Gate Length 240 nm 550 nm RF/microwave technology will be fundamentally influenced by nanotechnology.…”
Section: Mission Of Tc Mtt-25mentioning
confidence: 98%
“…Both threshold and memristive switching have their uses in neuromorphic circuits, and these effects can be linked to provide the necessary behaviors for use in programmable networks or as integrate-and-fire elements, in which the memristive memory integrates the incoming pulses and the threshold switch provides spiking behaviors (Mao et al, 2023). NDR responses in different materials have been shown to be programmable using the field effect in transistor geometry (Dragoman et al, 2008), and this programmability can be used to produce multivalued memory and dynamically reconfigurable logic operations (Sistani et al, 2021). Mixed volatility is generally a desirable property in many proposed neuromorphic circuits as it allows the systems to operate over a wide range of biologically relevant timescales from milliseconds to days (Gerstner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%